The Impact of the Farming Gardening Project Method Through Moving Classes on the Social and Emotional Behaviour of Kindergarten Age Children - Khosiah, Siti (Journal of Education Reseach and Evaluation, 2024)
This research problem focuses on the low ability of kindergarten B children in terms of cooperation, helping, discipline, self-confidence, and self-control. So, to overcome this problem, this study aims to analyze the impact of the farming gardening project method through moving classes on improving the social and emotional behavior of kindergarten B children. This type of research is an experiment with a quasi-experimental design. The research subjects comprised 40 kindergarten B children divided into two groups: an experimental group of 20 children and a control group of 20 children. Data collection methods used observation, interviews, and documentation studies. The research instruments included social and emotional behavior observation sheets and interview guides. Data were analyzed using statistical techniques with the help of the SPSS 12.0 for Windows program. The results showed that children in the experimental group who applied the farming gardening project method through moving class significantly improved social and emotional behavior compared to the control group who used conventional learning methods. Statistically, the difference in children's social and emotional behavior between the experimental and control groups was significant for social and emotional behavior. The conclusion of this study shows that the farming gardening project method through moving classes is efficacious in improving the social and emotional behavior of kindergarten B children. The implication of this study is the importance of applying project-based methods in learning activities to stimulate children's social and emotional development holistically.